‘Acting’ AOD: Spain faces a greater paralysis, if possible, to its international commitments to development cooperation - Cascante Hernández, Kattya (Revista Española de Desarrollo y Cooperación, 2023)
Almost a year since the universal Agenda the achieve of the goals (objectives sustainable development, OSD, 2015-30) started dawn, Spain not only drag all the ills of the international community, but adds homegrown, all irrelevance that the current caretaker government, wanted to provide to its policy of international cooperation for development over the last four years. An irrelevance that will make even more difficult to respond to international commitments, including the OSD Agenda.